Analisis Putusan Hakim Pada Tindak Pidana Perdagangan Orang Menggunakan Teori Tujuan Hukum Gustav Radbruch (Studi Kasus Putusan Nomor:487/Pid.Sus/2023/PN.Jambi) - Via Candritha; Abdul Bari Azed; M Muslih (Universitas Batanghari Jambi, 2026)
Human trafficking is a serious crime that violates human rights and has wide-ranging impacts on victims and society. In judicial practice, judges' rulings are expected not only to reflect legal certainty but also fairness and usefulness, as are the goals of law. This study aims to analyze the considerations judges take into account when sentencing perpetrators of human trafficking and to assess the application of Gustav Radbruch's legal theory goals, which include justice, legal certainty, and usefulness, in Ruling Number 487/Pid.Sus/2023/PN.Jambi. This research uses a normative juridical method with legislative, case, and conceptual approaches. Data were collected through a literature study of relevant laws and regulations, court rulings, and legal doctrines. Research results show that the judge's considerations in the decision were based on the applicable positive law, but have not fully reflected a sense of justice and the usefulness of the law, especially for the victims, when compared to other similar rulings. The relatively lighter sentence created an imbalance between the prosecutor's demands, the impact of the perpetrator's actions, and protection for the victims. Based on an analysis using Gustav Radbruch's theory, it can be concluded that these three fundamental legal values have not been fulfilled proportionally. Therefore, judges need to be consistent and careful in handing down sentences so that the decisions truly reflect substantive justice, provide legal certainty, and benefit society.